2007
DOI: 10.1111/j.1475-6773.2007.00760.x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Adverse Medical Events in VA Inpatient Care: Reliability Limits to Using Patient Safety Indicators as Performance Measures

Abstract: Objective. To assess Agency for Healthcare Research and Quality's Patient Safety Indicators (PSIs) as performance measures using Veterans Administration hospitalization data. Data Sources Study Setting. Nine years (1997Nine years ( -2005 of all Veterans Health Administration (VA) administrative hospital discharge data. Study Design. Retrospective analysis using diagnoses and procedures to derive annual rates and standard errors for 13 PSIs. Data Collection/Extraction Methods. For either hospitals or hospital n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…16 This concern has prompted the search for more direct approaches to measuring adverse events. Such approaches generally rely on more exhaustive physician or nurse reviews of a patient's complete medical record or chart.…”
mentioning
confidence: 99%
“…16 This concern has prompted the search for more direct approaches to measuring adverse events. Such approaches generally rely on more exhaustive physician or nurse reviews of a patient's complete medical record or chart.…”
mentioning
confidence: 99%
“…The search for more accurate measures of the scope of the problem continues (18). Administrative data such as the Agency for Healthcare Research and Quality's patient safety indicators (91) provide another source of data intended to fuel change; however, some evidence suggests that they do not predict individual hospital performance (171).…”
Section: External Motivatorsmentioning
confidence: 99%
“…Previous studies have cited coding issues as a significant factor limiting the use of the PSIs for public reporting and performance measurement. 22,39 We expected that the increased attention to coding postoperative complications might improve the PPV of some of the PSIs as compared to our previous results. The improvement in PPV for PE/DVT from 22% to 31% may reflect improvements in the documentation or coding of PE and DVT events, a focus of many healthcare systems, including the VA, following the introduction of the Surgical Care Improvement Program (SCIP) in 2005.…”
Section: Assessment Of Disagreementmentioning
confidence: 56%
“…[18][19][20] Studies have demonstrated good predictive and construct validity for several of the surgical PSIs. [21][22][23] Additionally, some of the surgical PSIs were recently endorsed by the National Quality Forum (NQF) for quality reporting and hospital performance measurement. 24 The Centers for Medicare and Medicaid Services (CMS) publicly report private sector PSI rates on the Hospital Compare website.…”
mentioning
confidence: 99%